ATHLETIC IDENTITY OF BOXERS OF DIFFERENT LEVELS OF MASTERY - Stanionis E. (Scientific and Educational Areas Under Modern Challenges, 2022)
this research aimed to investigate the peculiarities of the athletic identity of boxers of different levels of mastery. The study involved 30 average levels of mastery and 30 high levels of mastery sportsmen. The athletic identity measurement scale (AIMS-Plus) was used in the study. According to results of the study, the sportsmen of higher-level mastery have significantly higher level of athletic identity (p < 0,05) than sportsmen of average level of mastery. The sportsmen of higher-level mastery have higher level (p < 01) of social identity and positive affectivity. But the sportsmen of average level of mastery have higher level of negative affectivity and exclusivity (p < 01).
Keywords: мужчины; боксер; psychosocial adaptation; sports organization; спортивный идентитет; уровень спортивного мастерства; managers; trainers